Annual Review of Gerontology and Geriatrics, 10 (1990) : Biology of Aging. - Cristofalo, Vincent J. (Springer Pub. Co., 1990)
This volume presents a clear, concise overview of the current state of knowledge about the biology of aging - serving as both an invaluable graduate-level text and a key reference for practicing professionals. Over a dozen distinguished contributors probe the latest developments in our knowledge of why people age and how the process works. These authoritative chapters are not just written for biologists - but for gerontologists in general. Marks the tenth anniversary of the Annual Review of Gerontology and Geriatrics.